Intraoperative navigated ultrasound in posterior fossa surgery - Bopp Miriam; Saß Benjamin; Pojskic Mirza; Grote Alexander; Nimsky Christopher (Current Directions in Biomedical Engineering)
High navigation accuracy is a prerequisite for tailored and safe tumor resections. However, in posterior fossa surgery, especially in the semi-sitting position, navigation is often considered to be non-useful due to limited accuracy caused by gravitational effects and brain-shift. To enable navigation in these surgical approaches intraoperative evaluation of accuracy and navigation update strategies are required. Navigated intraoperative ultrasound (iUS) might serve as valuable tool to quantify navigation accuracy and even update navigation to gain higher accuracy. Data of 23 patients (28 lesions) undergoing navigation supported surgery in the posterior fossa with application of navigated iUS including acquisition of a 3D iUS data set were evaluated retrospectively based on intraoperative ratings on accuracy and tumor segmentation based on preoperative magnetic resonance imaging (MRI) and iUS data. In nine cases (eleven lesions) navigation was rated “insufficient” leading to a navigation update by manually outlining the tumor volumes within the iUS data set, whereas in all other cases navigation accuracy was rated “sufficient” with no need for further updates. Tumor volume was comparable between MRIand iUS-based segmentation. IUS was successfully applied in navigation-supported surgery in the posterior fossa in the semisitting position enabling continuous navigation-support throughout surgery by evaluation of navigation accuracy and navigation updates, supporting safe maximum tumor resection.